Biomimetically Enhanced Demineralized Bone Matrix for Bone Regenerative Applications - Ravindran, Sriram; Huang, Chun-Chieh; Gajendrareddy, Praveen; Narayanan, Raghuvaran (Frontiers in Physiology, 2015)
Demineralized bone matrix (DBM) is one of the most widely used bone graft materials in dentistry. However, the ability of DBM to reliably and predictably induce bone regeneration has always been a cause for concern. The quality of DBM varies greatly depending on several donor dependent factors and also manufacturing techniques. In order to standardize the quality and to enable reliable and predictable bone regeneration, we have generated a biomimetically-enhanced version of DBM (BE-DBM) using clinical grade commercial DBM as a control. We have generated the BE-DBM by incorporating a cell-derived pro-osteogenic extracellular matrix (ECM) within clinical grade DBM. In the present study, we have characterized the BE-DBM and evaluated its ability to induce osteogenic differentiation of human marrow derived stromal cells (HMSCs) with respect to clinical grade commercial DBM. Our results indicate that the BE-DBM contains significantly more pro-osteogenic factors than DBM and enhances HMSC differentiation and mineralized matrix formation in vitro and in vivo. Based on our results, we envision that the BE-DBM has the potential to replace DBM as the bone graft material of choice.